The Dynamics of Hired Farm Labour: Constraints and Community Responses 2002
DOI: 10.1079/9780851996035.0169
|View full text |Cite
|
Sign up to set email alerts
|

The role of the state in Manitoba farm labour force formation.

Abstract: This chapter examines the Canadian state's role in the development of Manitoba agriculture and specifically in the formation of ethnically based class fractions of the Manitoba farm labour force through a combination of agricultural, Indian and immigration policy. It argues that the state acts primarily in the interests of monopoly capital (agribusiness) and only secondarily in the interests of competitive capital (farmers) and the working class (farm labourers).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…37 In the United Kingdom, for example, access to migrant labor has allowed growers to intensify production through greater labor control, including the use of gangmasters, piece rates, and the extension of the work day (Ruhs, 2006b; Rogaly, 2008). In addition, research has also shown how migrant workers have been used to discipline domestic workers’ collective organizing (Martin, 1996; Mysyk, 2002; Plewa, 2007).…”
Section: Workplace Regimesmentioning
confidence: 99%
“…37 In the United Kingdom, for example, access to migrant labor has allowed growers to intensify production through greater labor control, including the use of gangmasters, piece rates, and the extension of the work day (Ruhs, 2006b; Rogaly, 2008). In addition, research has also shown how migrant workers have been used to discipline domestic workers’ collective organizing (Martin, 1996; Mysyk, 2002; Plewa, 2007).…”
Section: Workplace Regimesmentioning
confidence: 99%
“…Further, in 2000, SAWP workers accounted for 53 percent of total employment and an estimated 45 percent of total person hours in the agricultural industries using foreign workers (Weston and Scarpa de Masellis 2003). In Manitoba, there is also evidence that SAWP workers have displaced members of the domestic workforce, in particular First Nations groups (Mysyk 2002).…”
Section: Foreign Workers In Canadian Agriculturementioning
confidence: 99%
“…9 Domestic workers with other livelihood options simply do not choose to work in agriculture or use it only to supplement their income from full-time jobs. Throughout the twentieth century, farming operations in Canada were notorious for their inability to retain workers and their continued reliance on historically unfree 10 or marginalized sources of labor, including British orphans 11 , interned Japanese Canadians, German prisoners of war, conscientious objectors, and First Nation peoples (Bagnell 2001;Basok 2002;Mysyk 2002;Satzewich 1991;Wall 1992). Little appears to have changed: agriculture continues to persist as an unattractive employment opportunity for Canadian citizens.…”
Section: The Comparative Advantage Of Foreign Workersmentioning
confidence: 99%